Oxidative stress differentially impacts apical and basolateral secretion of angiogenic factors from human iPSC-derived retinal pigment epithelium cells - Lisheng Chen; N. Dayanthi Perera; Athanasios J. Karoukis; Kecia L. Feathers; Robin R. Ali; Debra A. Thompson; Abigail T. Fahim (Scientific Reports, 2022)
Abstract The retinal pigment epithelium (RPE) is a polarized monolayer that secretes growth factors and cytokines towards the retina apically and the choroid basolaterally. Numerous RPE secreted proteins have been linked to the pathogenesis of age-related macular degeneration (AMD). The purpose of this study was to determine the differential apical and basolateral secretome of RPE cells, and the effects of oxidative stress on directional secretion of proteins linked to AMD and angiogenesis. Tandem mass tag spectrometry was used to profile proteins in human iPSC-RPE apical and basolateral conditioned media. Changes in secretion after oxidative stress induced by H2O2 or tert-butyl hydroperoxide (tBH) were investigated by ELISA and western analysis. Out of 926 differentially secreted proteins, 890 (96%) were more apical. Oxidative stress altered the secretion of multiple factors implicated in AMD and neovascularization and promoted a pro-angiogenic microenvironment by increasing the secretion of pro-angiogenic molecules (VEGF, PTN, and CRYAB) and decreasing the secretion of anti-angiogenic molecules (PEDF and CFH). Apical secretion was impacted more than basolateral for PEDF, CRYAB and CFH, while basolateral secretion was impacted more for VEGF, which may have implications for choroidal neovascularization. This study lays a foundation for investigations of dysfunctional RPE polarized protein secretion in AMD and other chorioretinal degenerative disorders.